THE POPULARIZING FACTORS OF MUSLIM WOMEN’S WEAR IN INDONESIA: From Politic, Media to Fashion (JOURNAL OF INDONESIAN ISLAM, 2023)
This article focuses on exploring factors behind the rising popularity of veiling during the 2000s. The surging fame of the women’s Muslim wear is stimulated by the changing trend within the political realm marked by the resurgence of political Islam. These alterations in the political milieu prompted corresponding adjustments in the government's stance towards Islam. Notably, there was a more accommodating approach reflected in policy reforms concerning religious matters. In addition, there are other factors that lead to the rising fame of veil among Indonesian Muslims including media, fashion as well as the celebrity factor. Media in all forms indeed play influential role in promoting the veil with songs, movies and magazines exposing the veil in a positive light. Interestingly, the songs and movies tend to use the encouragement rather obliging the veil; they ways used by the policy. Further usage by celebrity then lead to the extent where the veil becomes common. An interesting yet ironic fashion development turns out to be source for criticism as some of them deemed to be inappropriate. Still, the trend shows that veil has become common to the extent that the emergence of variety is inevitable.